THE EFFECT OF DIFFERENT CONCRETE MIX DESIGNS AND MAXIMUM AGGREGATE SIZE VARIATIONS ON THE COMPRESSIVE STRENGTH OF NORMAL CONCRETE (GEOMATE Journal, 2024)
Each component of the material that makes up concrete has a significant influence on its mechanical properties, so a mix design is needed to obtain the optimum concrete quality. This research uses three mix design methods, namely based on SNI 03-2834-2000, SNI 7656:2012, and Dreux Gorisse. SNI 03-2834-2000 refers to the DOE method from the UK, while SNI 7656:2012 adopts the ACI method from America. SNI 03-2834-2000 and SNI 7656:2012 are the applicable methods in Indonesia. While Dreux Gorisse is a concrete mix design method originating from France. This study aims to analyze the effect of concrete mix design and maximum aggregate size variation on the compressive strength of normal concrete. The maximum size of coarse aggregate used was 10, 20, and 40 mm. The planned concrete quality (f'c) was 25 MPa with cylindrical specimens measuring 15x30 cm. The highest compressive strength test results at the age of 28 days are with the SNI 7656:2012 method for a maximum aggregate size of 10 mm at 31.33 MPa. While the lowest compressive strength value with Dreux Gorisse for a maximum aggregate size of 40 mm was 25.38 MPa. In all mix design methods, the smaller the maximum size of coarse aggregate, the higher the compressive strength value. The maximum aggregate size of 10 mm in the SNI 7656:2012 method resulted in an increase in the maximum compressive strength by 25.31% from the planned compressive strength because it has a lower w/c ratio and slump values of 0.49 and 65 mm.